Evaluation of the impact of the feed-in generation in the prices of the Iberian Electricity Market in 2013 - João Tomé Saraiva (2016)
Power industry has been deeply restructured in recent decades. Along this period vertically integrated structures evolved to more disaggregated models in which some activities are now provided under competition as generation and retailing while some others are provided under regulated monopolies as network transmission and distribution. Simultaneously, most countries started to encourage the use of renewable sources, namely to cope with environmental issues and to enlarge the energy independency. Having in mind these ideas and given the development of the Iberian Electricity Market and the increase of the installed capacity in units paid by feed-in tariffs, it becomes important to estimate the impact of this feed-in generation in the market prices. This paper describes the approach that was developed to estimate this impact and the implemented software application. This application was then used to evaluate the impact on prices on all trading hours of 2013 of the Portuguese photovoltaic generation, the Portuguese wind generation, all the Portuguese feed-in generation and also all the Iberian feed-in generation.